2021
DOI: 10.1002/adsu.202100113
|View full text |Cite
|
Sign up to set email alerts
|

Crop root Exudate Composition‐Dependent Disassembly of Lignin‐Fe‐Hydroxyapatite Supramolecular Structures: A Better Rhizosphere Sensing Platform for Smart Fertilizer Development

Abstract: avoid food shortages. However, the implementation of intensive agricultural practices such as excessive irrigation, tillage, and chemical fertilizers to increase crop productivity has devastated soil and farmland quality. [1,2] Particularly, acidification, salinization, and organic matter decomposition in soils typically coincide with agriculture practices, which adversely affect crop productivity and soil fertility. [3][4][5] Additionally, the inefficient absorption of conventional chemical NPK (i.e., nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It needs to be emphasized that the interaction of BPA-HP copolymeric precipitates and radish root was associated with the mild stress-triggered responses at the root surface by the accumulation and decomposition processes of BPA-HP copolymers. ,, These results demonstrated that the formed BPA-HP copolymeric precipitates by E-PH had a huge potential to be used in agricultural productivity. Further research should be focused on (1) the radioactive labeling of H-LBs to track their movement in plant roots, (2) the development of a rhizosphere sensing platform to detect the relationship between root exudates and H-LBs, (3) the main targets of H-LBs in plant-growth promotion to uncover plant hormone pathways and gene-enzyme relationships, and (4) the practical application of H-LBs in soil amelioration to enhance agricultural productivity and sustainability. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It needs to be emphasized that the interaction of BPA-HP copolymeric precipitates and radish root was associated with the mild stress-triggered responses at the root surface by the accumulation and decomposition processes of BPA-HP copolymers. ,, These results demonstrated that the formed BPA-HP copolymeric precipitates by E-PH had a huge potential to be used in agricultural productivity. Further research should be focused on (1) the radioactive labeling of H-LBs to track their movement in plant roots, (2) the development of a rhizosphere sensing platform to detect the relationship between root exudates and H-LBs, (3) the main targets of H-LBs in plant-growth promotion to uncover plant hormone pathways and gene-enzyme relationships, and (4) the practical application of H-LBs in soil amelioration to enhance agricultural productivity and sustainability. , …”
Section: Resultsmentioning
confidence: 99%
“…19,27,46 These results demonstrated that the formed BPA-HP copolymeric precipitates by E-PH had a huge potential to be used in agricultural productivity. Further research should be focused on (1) the radioactive labeling of H-LBs to track their movement in plant roots, (2) the development of a rhizosphere sensing platform to detect the relationship between root exudates and H-LBs, 47 (3) the main targets of H-LBs in plant-growth promotion to uncover plant hormone pathways and gene-enzyme relationships, and (4) the practical application of H-LBs in soil amelioration to enhance agricultural productivity and sustainability. 19,48 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Root Length and Gi Assessment Of Bpa-hp Precipitatesmentioning
confidence: 99%
“…The prolonged release effects with incubation times of up to 56 days were also typical of the surface engineering of P-containing ceramics. 10,35,36 It is important to note that the MVOC-induced increase in the available P in the soil even occurred without adding calcium phosphate powder (Figure S6B), indicating that the inherent P-containing minerals of the soil are strongly affected by the MVOCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Inherent absorbances of the powders in the solutions at 420 nm were compensated. Total phenolic contents were assessed as described previously ( 38 ). Briefly, the powders (15 mg of selected fungal cultures, 3 mg of microbial consortia, and the corresponding amounts of the controls) were dissolved in distilled water (2.25 mL) containing Folin-Ciocalteu phenol reagent (0.25 mL).…”
Section: Methodsmentioning
confidence: 99%